PENGARUH KOMBINASI DOSIS BIOCHAR SEKAM PADI DAN VOLUME PEMBERIAN AIR TERHADAP P-TERSEDIA, SERAPAN P DAN HASIL LOBAK PADA TANAH BERKAPUR DI PULAU TIMOR - Ady K. Mata Ratu; Diana Y. L. Serangmo; Yoke I. Benggu (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Nusa Cendana, 2021)
Dryland farming in Timor island is always constrained with the shortage of water supply, soil fertility as well as the availability of nutrients especially Phosphor (P). This condition can be eliminated by application of organic matterial to soil, because organic matter can increase the soil’s ability to hold water and soil fertility. Biochar as an organic material has been proved to increase soil water holding capacity and able to adsorb nutrients to prevent it from leaching. This research aimed to study the effect of combination of biochar and water supply on the availability of P in soil, uptake P by plants and yields of Turnip planted ini calcareous soil of Timor . This research is designed using Completely Randomized Design (CRD) and it is a single factor trial. There are 7 treatments of a combination of rice husk biochar dosage and volume of water supply. The results showed that there is a significant effect of the combination of rice husk biochar dosage and volume of water supply on the availability of soil P and the weight of radish tubers. Application of 300 gram.polybag-1 of biochar + 90% Etm of water supply gave higher available P (87,22 ppm), while application of 300 gram.polybag-1 of biochar + 80% Etm of water supply gave a better fresh weight of tuber (305,00 g ) compare to other treatments.